2011
DOI: 10.4049/jimmunol.1100264
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IL-21 Receptor on B Cells and IL-21 Secretion Distinguishes Novel 2009 H1N1 Vaccine Responders from Nonresponders among HIV-Infected Persons on Combination Antiretroviral Therapy

Abstract: Mechanisms underlying failure of novel 2009 H1N1 influenza vaccine-induced Ab responses in HIV-infected persons are poorly understood. This study prospectively evaluated 16 HIV-infected patients on combination antiretroviral therapy and eight healthy controls (HC) who received a single 15 μg dose of nonadjuvanted novel 2009 H1N1 influenza vaccine during the 2009 H1N1 epidemic. Peripheral blood was collected at baseline (T0) and at 7 d (T1) and 28 d (T2) postvaccination for evaluation of immune responses. Preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 71 publications
(94 reference statements)
3
89
1
1
Order By: Relevance
“…Interestingly, among all individuals who did not increase (Delta − ) the ALA titres after vaccination, higher levels of B cell IL-21R expression and plasma IL-21 with lower levels of MA and DN were observed compared to individuals who had an increased (Delta + ). Moreover, while a direct correlation was found between B cell IL-21R expression and ALA titres before vaccination, this reversed after vaccination, thus reinforcing the positive role indicated previously for the B cell IL-21R during vaccination [14]. The frequencies of both MA and DN correlated directly with the ALA titres after vaccination and inversely to B cell IL-21R expression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, among all individuals who did not increase (Delta − ) the ALA titres after vaccination, higher levels of B cell IL-21R expression and plasma IL-21 with lower levels of MA and DN were observed compared to individuals who had an increased (Delta + ). Moreover, while a direct correlation was found between B cell IL-21R expression and ALA titres before vaccination, this reversed after vaccination, thus reinforcing the positive role indicated previously for the B cell IL-21R during vaccination [14]. The frequencies of both MA and DN correlated directly with the ALA titres after vaccination and inversely to B cell IL-21R expression.…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported recently that the up-regulation of IL-21 receptor (R) on B cells and of plasma IL-21 levels could distinguish among A(H1N1)pdm09 vaccine responders and non-responders [14]. Thus, in order to assess whether the ALA increase observed in the HIV and KT groups after flu immunization, related to a different activation status of B cells or to a different degree of immune senescence in these groups, the B cell IL-21R expression and the frequencies of mature-activated (CD10 cells was significantly higher in the HC group compared to HIV and KT (P < 0·0001), with the lowest level observed in the HIV group compared to KT (P = 0·02) (Fig.…”
Section: B Cell Immune Activation and Senescence In The Different Patmentioning
confidence: 99%
“…54 Consistent with this premise, previous studies have shown decreased serum IL-21 and IL-21 production by T cells from HIV-infected individuals. 55,56 Although we found no difference in expression of IL-21 among Tfh cells from LNs of SIV-uninfected and SIV-infected RMs, preferential infection of Tfh cells could alter the overall functionality of these cells, thereby potentially affecting the ability to mount appropriate adaptive immune responses.…”
Section: Discussionmentioning
confidence: 40%
“…For example, one of these studies proposed upregulation of the interleukin (IL)-21 receptor on B-cells and of IL-21 in plasma as a novel immunological marker to distinguish between 2009 pandemic flu vaccine responders and non-responders. 90 This may suggest that additional immunonological markers, rather than antibody response, may be used for evaluating clinical protection in the HIV-1 infected pediatric population.…”
Section: Measles Mumps Rubella (Mmr)mentioning
confidence: 99%